Exploring hidden narratives: Conscript graffiti at the former military base of Kummersdorf. (February 2013) - Merrill, Samuel; Hack, Hans
This article explores the cultural significance and interpretative potential of graffiti left by Soviet conscripts at Kummersdorf, a former military base in the German federal state of Brandenburg. The graffiti is framed as war art and its typology, distribution and content is studied in detail. In this way opportunities for further research are highlighted, as well as the potential for the graffiti to contribute to interpretative and conservation strategies. We demonstrate how the graffiti embodies multi-level interpretative narratives which can help to reveal hidden aspects of Soviet conscript life and cultural practices whilst alluding to global events and Soviet and Russian military policy. More generally, the article aims to promote the potential of graffiti and other forms of what is traditionally considered vandalism to contribute to the cultural significance and interpretation of heritage sites.